DEFORESTATION ISSUE CONSTRUCTION FROM THE TAKNALAWE’ EPIC OFDAYAKKAYAAN WEST KALIMANTAN - Budi, Budi; Herdiani, Een; Heriyawati, Yanti (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2023)
Takna' Lawe' is an oral tradition of the Kayaan people. Lii' Long and Ding Ngo wrote down this oral tradition in a book entitled Poetry Lawe'. The epic Takna' Lawe' is famous for the story of heroism and love from the figure of Lawe'. Apart from this story, there are also signs from the Takna' Lawe epic which constructs the issue of deforestation. This study is focused on the interpretation of the signs in the episode